Dissonance as a productive force in the emergence of alternative crisis support and impetus for social change—principles and organizational form of the association Open Dialogue Leipzig e.V. - Thomas Klatt; Lea Goncalves Crescenti; Therese Kruse; Irene Nenoff-Herchenbach; Sarah Schernau; Sebastian von Peter (Frontiers in Psychology)
IntroductionThis article examines the productivity of dissonance in the development of alternative crisis intervention methods, using the German example of the “Open Dialogue Leipzige.V.” The research provides detailed insights into the development of the association and the adaptation of the OD approach to local circumstances.MethodsThe presentation is based on a participatory research process, primarily processing interview data using the Grounded Theory Method. It analyzes the specific practices of implementing Open Dialogue within the association and the organizational and contextual conditions corresponding with it.ResultsDespite the challenges accompanying the introduction and sustainability of Open Dialogue in the German healthcare system, the organizational structure of the association—characterized by grassroots democratic principles and a community driven by a strong willingness to change—enables a successful application of Open Dialogue principles.DiscussionThe article critically illuminates how engagement, professionalization, and participatory learning mutually influence each other through the organizational form of the association, bringing forth an innovative crisis intervention that could potentially serve as a model for other contexts.